Teacher Transition into Innovative Learning Environments A Global Perspective - Imms, Wesley; Kvan, Thomas (Springer Nature Singapore : Imprint: Springer, 2021)
This open access book focuses on how the design and use of innovative learning environments can evolve as teaching practices and education policies change. It addresses how these new environments are used, how teachers are adapting their practices, the challenges that these changes pose, and the effective evaluation of these changes. The book reports on emerging research in learning environments, with a particular emphasis on how teachers are transitioning from traditional classrooms to innovative learning environments. It offers a significant evidence-based global assessment of current research in this field by designers, architects, educators and policy makers. It presents twenty-five cutting-edge projects from researchers in fifteen countries. Thanks to the book's comprehensive international perspective, which combines theory and practice in a single publication, readers will gain a wealth of new insights.